(untitled) (Medical Forum Monthly, 2023)
Objective: The objective of this study was to determine the frequency of empyema after tube thoracostomy in patients presenting with penetrating chest trauma. Study Design: Descriptive Study Place and Duration of Study: This study was conducted at the Department of Thoracic Surgery, MTI/Lady Reading Hospital, Peshawar, Pakistan from 1st October 2022 to 31st March 2023. Materials and Methods: The study included 103 patients aged 18 to 60 years of both genders who underwent tube thoracostomy for penetrating chest injury. The study collected baseline information of patients including age, gender, BMI, site of tube, duration of tube placement, and indication for tube placement. Patients were followed up from the time of tube placement till discharge, and those who developed chest pain, fever, and shortness of breath underwent chest radiography. Results: A total of 103 patients were included in the study, with a mean age of 40.42 years and a mean BMI of 22.89. The duration of tube insertion ranged from 1 to 15 days, with a mean duration of 4.99 days. Of the total patients, 21 (20.4%) developed empyema, while 82 (79.6%) did not. Post-stratification analysis showed that BMI and duration of tube insertion were significant predictors of empyema development, with a p-value of 0.002 and 0.001, respectively. Age category, gender, location, and indication for tube placement were not significant predictors of empyema development. Conclusion: The incidence of empyema was found to be 20.4%. The duration of tube insertion and BMI were found to be statistically significant risk factors for the development of empyema in these patients.